Precision cancer sono-immunotherapy using deep-tissue activatable semiconducting polymer immunomodulatory nanoparticles - Li, Jingchao (2023)
Nanomedicine holds promise to enhance cancer immunotherapy; however, its potential to elicit highly specific anti-tumor immunity without compromising immune tolerance has yet to be fully unlocked. This study develops deep-tissue activatable cancer sono-immunotherapy based on the discovery of a semiconducting polymer that generates sonodynamic singlet oxygen (1O2) substantially higher than other sonosensitizers. Conjugation of two immunomodulators via 1O2-cleavable linkers onto this polymer affords semiconducting polymer immunomodulatory nanoparticles (SPINs) whose immunotherapeutic actions are largely inhibited. Under ultrasound irradiation, SPINs generate 1O2 not only to directly debulk tumors and reprogram tumor microenvironment to enhance tumor immunogenicity, but also to remotely release the immunomodulators specifically at tumor site. Such a precision sono-immunotherapy eliminates tumors and prevents relapse in pancreatic mouse tumor model. SPINs show effective antitumor efficacy even in a rabbit tumor model. Moreover, the sonodynamic activation of SPINs confines immunotherapeutic action primarily to tumors, reducing the sign of immune-related adverse events.